Effects of drugs commonly used in Sars-CoV-2 infection on renal tissue in rats (Annals of Medical Research, 2023)
Aim: In December 2019, the coronavirus disease was caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Some drugs were repurposed for this disease treatment. Hydroxychloroquine (HCQ), favipiravir (FAV), molnupiravir (MOL), and dexamethasone (DEX) were widely used for the treatment of the disease. To increase the success of the treatment of coronavirus disease, there was used some of these drugs in combination. On the other hand, limited studies report these drugs’ side effects. Therefore, this study was designed to evaluate the possible effects of these drugs and their combinations on the kidney tissues of rats without viral load.Materials and Methods: Male Wistar albino rats were divided into control, HCQ, FAV, HCQ+FAV, HCQ+FAV+DEX, MOL, and MOL+DEX groups. At the end of the experiment, the serum kidney tissue samples were taken. Serum samples were analyzed for urea and creatinine. Kidney tissue samples were assessed as histopathological and immunohistochemical for heat shock protein 60 (HSP60), caspase-3, and receptor-interacting protein kinase-3 (RIPK3).Results: Urea and creatinine levels were within the normal range in all groups. Histopathologically, all drugs and their combinations caused tubular degeneration. On the other hand, histopathological alterations were more prominent in the HCQ group. The oxidative stress marker HSP60 was significantly increased in FAV, MOL, and MOL+DEX groups, while it was similar to the control group in the HCQ groups. Apoptosis marker caspase-3 expression was found to be prominently higher in other drug groups except the FAV group. Expression of RIPK3, a marker of necroptosis, was significantly increased in all drug groups.Conclusion: Taken together, the data of our study show that the administration of all drugs alone and in combination may cause structural damage to the kidney. Furthermore, our results indicate that HCQ can exhibit more damaging effects compared to other drugs.
Keywords: SARS‐CoV‐2; Hydroxychloroquine; Favipiravir; Molnupiravir; Dexamethasone; Kidney damage